English Pronunciation by Korean EFL Learners on Hilokal Language Educational Application - Cahyaningrum, Aulya (Elsya : Journal of English Language Studies, 2023)
English is being learned for several purposes by people globally embody some different accents; therefore, this study analyse the English pronunciation by Korean learners on English learning application classes since Korea is still having lack of perfect English standard pronunciation with its identity of developed industry country. Consequently, this study aims to investigates Korean-English phenomenon on Hilokal application as most English learners there by comparing the differences between original English sounds and Korean using descriptive qualitative from the audio recordings has been collected. The result shows that all 7 Korean learners (age range of 20-35) still produce some different sounds from the standard English ones noted as International Phonetic Alphabet (IPA) because of the differences in the writing systems of the two languages and the alphabet of Korean itself. There are five places of articulations: labiodental, alveolar, post-alveolar, bilabial, and palatal seized from some processes such as replacement, addition, and omission in producing the word sounds. Furthermore, the dominant difference in sounds is in sound addition /ə/ or /ɪ/ with 27 items and 17 items from loan words. The implications of this study are fresh data focus on phonology analysis and can be useful in English teaching practice for foreign languages in order to have close resemblance English pronunciation to have more intelligibility with the standard patented.